Kesiapsiagaan Bencana Berbasis Komunitas Perkotaan - Aprilyanto Aprilyanto; Rio Khoirudin Apriyadi; Tri Winugroho; I Dewa Ketut Kerta Widana; Wilopo Wilopo (University of Bengkulu, 2021)
[Urban Community-based Disaster Preparedness] Geographical, hydrological, demographic, and sociological conditions of Indonesia make Indonesia's territory prone to disasters (natural, non-natural, and social). The history of disasters shows a trend of increasing the number of victims and types of disasters. Various efforts are needed in anticipating the possibility of a disaster that will occur, so that preventing risks, reducing risks or even eliminating disaster risks by reducing vulnerability and or increasing the limited capacity of the community is the simplest solution to the complexity of the disaster problem. Disaster risk is the probability of a potential disaster with the consequent damage being a key element. A threat (danger) only becomes a disaster if it affects vulnerable communities. The community is a key element in dealing with disasters, besides being the first to know about a disaster incident, the community is not only an object but also a subject that must be empowered in disaster management. This means that whatever efforts in disaster management must lead to the community. Strategies are needed to increase community resilience to an increasing number of disaster risks. Pre-disaster mitigation and preparedness activities are needed to reduce the vulnerability of a community and to protect the community whenever a disaster occurs. This research contributes to the current knowledge of the urban community preparedness index in terms of disaster preparedness. This descriptive quantitative research uses univariate analysis as the blade of analysis with a sample of 204 respondents who live in the DKI Jakarta area, and were selected randomly. This study uses primary data. Data collection was carried out through an online google form questionnaire directly to residents of DKI Jakarta Province. The results showed that the population of DKI Jakarta Province has various socio-economic characteristics, 77.94% of respondents have had disaster experience, 46.67% of the Material Preparedness Index, 82.52% of the Knowledge and Awareness Index for Preparedness, and 52.94% of the Preparedness Index. Act. Therefore, disaster risk reduction requires the efforts of all stakeholders such as the community (individuals and communities), government agencies, non-governmental organizations (NGOs), and even the business world.